Pengaruh Pembelajaran PAI terhadap Hasil Belajar Siswa: Tinjauan Meta Analisis - Taridala, Sri Marliah Puteri; La Fua, Jumarddin; Wahyuni, Imelda (Shautut Tarbiyah-IAIN Kendari, 2026)
This study presents a meta-analysis review to measure the effect of Islamic Religious Education (PAI) learning on student learning outcomes. The analysis was conducted by synthesizing empirical findings from various previous studies to provide a comprehensive and objective overview. The results indicate that PAI learning has a significant impact on student learning outcomes. The strongest and most consistent influence is found in the affective-spiritual domain, particularly in the formation of character, religious attitudes, and discipline, with many effect size values categorized as large. The subject of Akidah Akhlak (Islamic Creed and Morals) is identified as the key component most effective in shaping student character. Furthermore, an analysis stratified by educational level reveals varying patterns of effectiveness. PAI learning shows a broad and strong impact at the Elementary School (SD) level, contributing to increased motivation and basic academic achievement. At higher levels, its impact becomes more specialized, such as enhancing problem-solving abilities in Junior High School (SMP) and deepening spiritual values in Islamic Senior High School (Madrasah Aliyah/MA). These findings imply that strengthening PAI learning needs to focus on a holistic approach that emphasizes value internalization and implements differentiated learning designs according to the developmental stage of learners at each educational level